Rag-Pickers as Benefactors and Beneficiaries of the Sustainable Development Goals: A Brief Literature Review - Venkatesh, G (Studia Ecologiae et Bioethicae, 2023)
Ragpickers have long led a marginalised, subliminal and deprived existence, and have silently gone about contributing to ‘informal waste recycling’, diverting in many cities and towns, over half of the recyclable wastes from dumpsites to the technosphere. The reviewer has based this paper on 60 peer-reviewed publications spanning a time period of 28 years – from 1995 – 2022, originating from over a dozen different countries, and encompassing the social, economic and environmental dimensions of sustainability. The discussion has been structured around the six question words – Where/Wherefrom, When, How, What, Why and Who/Whom. While there is no claim of any addition per se being made to the extant body of knowledge, the reviewer would like to describe this as an attempt to simply collate existing knowledge to serve the practical purpose of highlighting the plight of our impoverished, malnourished, oppressed brethren, to elicit appreciation, understanding and support for them, from policymakers in government, CSR personnel from the corporate world, journalists in the media, and most importantly, from the common urban denizens. All these entities can work shoulder to shoulder with the NGOs who have been relentlessly striving to help the rag-pickers to ‘stay afloat’. The reviewer fondly hopes that this will motivate more concerted transdisciplinary applied research predicated on the Sustainable Development Goals – a collaboration among the disciplines of healthcare, sociology, psychology, urban planning, sustainable development, environmental engineering, and even art and poetry.